PENGARUH KUALITAS JASA TERHADAP KEPUASAN, REPUTASI MEREK DAN LOYALITAS PENGGUNA KARTU SIM PRABAYAR TELKOMSEL (Studi pada Segmen Remaja di Kota Denpasar) - Santosa, I Made Nugraha; Suprapti, Ni Wayan Sri; Giantari, I Gusti Ayu K. (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.05.NO.08. TAHUN 2016, 2016)
The development of business very quickly and rapidly provide an opportunity or a threat to the businesses to be able to sustain its business and in order to win the competition. The aim of this rasearch is to explain the influence  of service quality on customer satisfaction, brand reputation and customer loyalty on youth customer prepaid sim card of Telkomsel in Denpasar.The subjects of this research is Telkomsel prepaid sim card users, with a sample of 120 people. The samples were collected by using non probability sampling method and purposive sampling technique. Data were analyzed using the technique SEM (Structural Equation Modelling).The results of this research shows that the quality of services significantly and positively influence on customer loyalty, customer satisfaction and reputation of the brand. Customer satisfaction significantly and positively influence  on the reputation of the brand and customer loyalty. Brand reputation are also significantly and positively influence on customer loyalty
Keywords: Telkomsel, Quality of Service, Customer Satisfaction, Brand Reputation and Customer Loyalty